THE EFFECT OF FUNDAMENTAL FINANCIAL FACTOR TO STOCK RETURN (STUDY ON CONSUMER GOODS INDUSTRY SUB SECTOR FOOD AND BEVERAGES WHICH IS LISTED AT INDONESIA STOCK EXCHANGE IN 2011 – 2016) - Cepi Pahlevi Pahlevi (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2018)
The purpose of this study is to find the effect of fundamental financial factor to stock return of the listed consumer goods industry sub-sector food and beverages companies at Indonesia Stock Exchange 2011-2016. Variables that are used to measure the fundamental factor are Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity (ROE), and Total Asset Turnover (TATO) to Stock Return as dependent variable. Population of this study is food and beverage sub sector companies at Indonesia Stock Exchange 2011-2016, with total of 17 companies. Sampling method used was purposive sampling with total of 11 companies. This research used multiple regression analysis method and hypothesis testing (F test and T test) with significant level of 5% alpha. The result of this study, shows that CR, DER, TATO have a negative and have not significant effect to stock return. ROE variable has a positive and significant effect to stock return. Based on the R square test, 20.4% stock return is explained by fundamental financial factors.